The Role of the Na+/Ca2+ Exchanger in Aberrant Intracellular Ca2+ in Cardiomyocytes of Chagas-Infected Rodents - Lopez, Jose R.; Linares, Nancy; Adams, Jose A.; Mijares, Alfredo (Frontiers in Cellular and Infection Microbiology, 2022)
Chagas disease produced by the parasite Trypanosoma cruzi constitutes an important public health threat in Latin America. We have shown that cardiomyocytes from patients with Chagas cardiomyopathy have a chronic elevation of the diastolic Ca2+ concentration ([Ca2+]d), associated with cardiac dysfunction. We explored the role of the Na+/Ca2+ exchanger (NCX) in C57BL/6 mice infected with the T. cruzi Y strain. Infected (positive parasitemia) and uninfected mice were anesthetized (ketamine/xylazine) and sacrificed by cervical dislocation at 20-, 40- and 120- days post-infection (dpi). Intracellular Ca2+ was measured using Ca2+ selective microelectrodes in enzymatically dissociated cardiomyocytes from control mice (CONT), and cardiomyocytes from T. cruzi infected mice (IM) in the early acute phase (IMEAP) at 20 dpi, in the acute phase (IMAP) at 40 dpi, and in the chronic phase (IMCP) at 120 dpi. Like Chagas human cardiomyocytes, [Ca2+]d was 1.6 times higher in IMEAP, 2.6 times in IMAP, and 3.9 times in IMCP, compared to CONT cardiomyocytes. To explore the activity of NCX in the reverse mode, we replaced extracellular Na+ in equivalent amounts with N-methyl-D-glucamine. The reduction of [Na+]e to 65 mM caused an increase in [Ca2+]d of 1.7 times in CONT, 2 times in IMEAP, 2.4 times in IMAP, and 2.8 in IMCP cardiomyocytes. The Na+ free solution caused an elevation of [Ca2+]d of 2.5 times in CONT, 2.8 times in IMEAP, 3.1 times in IMAP, and 3.3 times in IMCP cardiomyocytes. Extracellular Ca2+ withdrawal reduced [Ca2+]d in both CONT and infected mice cardiomyocytes and prevented increases in [Ca2+]d induced by Na+ depletion. To elucidate the mechanisms involved in the elevation of [Ca2+]d in Na+-free media, the effect of two blockers of the NCX reverse, KB-R7943 and YM-244769, was studied. Both NCX blockers reduced [Ca2+]d in IMEAP, IMAP, and IMCP cardiomyocytes and prevented the increase in [Ca2+]d associated with exposure to a solution without Na+. These results suggest that Ca2+ entry through NCX reverse mode plays a significant role in observed intracellular dyshomeostasis in infected cardiomyocytes. Furthermore, NCX inhibitors may be a viable therapeutic approach for treating patients with Chagas cardiomyopathy.